2020
DOI: 10.21203/rs.3.rs-33743/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic Genome-Wide Association Analysis and Identification of Candidate Genes Involved in Anaerobic Germination Tolerance in Rice

Abstract: Background: In Asian rice production, an increasing number of countries now choose the direct seeding mode because of rising costs, labour shortages and water shortages. The ability of rice seeds to undergo anaerobic germination (AG) plays an important role in the success of direct seeding.Results: In this study, we used 2,123,725 single nucleotide polymorphism (SNP) markers based on resequencing to conduct a dynamic genome-wide association study (GWAS) of coleoptile length (CL) and coleoptile diameter (CD) in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Prior genome-wide association studies (GWAS) on germplasm panels and genetic mapping studies on biparental populations have been conducted to identify quantitative trait loci (QTLs) for phenotypes associated with deep-sowing tolerance in rice, including mesocotyl length (Wu et al, 2015a;Zhao et al, 2018;Liu et al, 2020), seedling vigor (Guo et al, 2019), and anaerobic germination (Yang et al, 2019;Rohilla et al, 2020;Su et al, 2020). From five GWAS studies of mesocotyl length using rice diversity panels ranging in size from 147 to 621 individuals, ~64 marker-trait associations (18 QTLs and 46 loci) have been reported, with overlap among some traitassociated genomic regions from different studies yielding a minimum of eleven uniquely identified QTL/loci overall (Wu et al, 2015a;Lu et al, 2016;Zhao et al, 2018;Liu et al, 2020;Wang et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…Prior genome-wide association studies (GWAS) on germplasm panels and genetic mapping studies on biparental populations have been conducted to identify quantitative trait loci (QTLs) for phenotypes associated with deep-sowing tolerance in rice, including mesocotyl length (Wu et al, 2015a;Zhao et al, 2018;Liu et al, 2020), seedling vigor (Guo et al, 2019), and anaerobic germination (Yang et al, 2019;Rohilla et al, 2020;Su et al, 2020). From five GWAS studies of mesocotyl length using rice diversity panels ranging in size from 147 to 621 individuals, ~64 marker-trait associations (18 QTLs and 46 loci) have been reported, with overlap among some traitassociated genomic regions from different studies yielding a minimum of eleven uniquely identified QTL/loci overall (Wu et al, 2015a;Lu et al, 2016;Zhao et al, 2018;Liu et al, 2020;Wang et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%